THE SWABIAN DIALECT IN THE GERMAN LANGUAGE ISLAND IN RUSSIA - Bukharov , Valeriy; Baykova, Olga; Obukhova, Olga (Revista Inclusiones, 2020)
The article describes the changes in the phonetic system of German dialects in conditions of multifold migrations of German settlers around Russia that have taken place since the beginning of the XX century. As a result of dialect mixing, one can observe the process of development of new regional variants. The description is based on the dynamics of changes in Swabian dialects, since they are represented in various regions of Russia and have been exposed to the most significant influence from other dialect groups which are more numerous. The article describes the migration of the Swabian German speakers deported in the early 40s and the development of regiolects based on the Swabian dialect in Russia and Kazakhstan. The empirical material of the study are the lexical items containing Swabian diphthongs from various regions of Russia and the CIS states, as well as from modern German dictionaries and reference books.